2019
DOI: 10.1177/0305735619835019
|View full text |Cite
|
Sign up to set email alerts
|

On music’s potential to convey meaning in film: A systematic review of empirical evidence

Abstract: With its schema-activating potential to influence an audience’s perception and interpretation of film plot and protagonists, film music goes far beyond the role of an emotionalizing accessory in film contexts. For this review, 24 German and English empirical studies that tested music’s potential to convey meaning were identified to be compared in their research questions, the characteristics of their methods, designs, samples, and stimulus materials, as well as main results. Depending on the degree of realism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 90 publications
(222 reference statements)
0
17
0
1
Order By: Relevance
“…These studies represent an attempt to fill in the theoretical and methodological gaps reported by Herget’s (2019) review. Although our results seem very promising, further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies represent an attempt to fill in the theoretical and methodological gaps reported by Herget’s (2019) review. Although our results seem very promising, further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This results in experiments each analyzing a single psychological construct. (2) Complex psychological constructs such as sympathy and empathy toward media protagonists could and should be investigated through all the available established measuring instruments (Herget, 2019). (3) There are hardly any ecologically valid investigations carried out in natural contexts such as during a visit to the cinema, a television evening with the whole family, or alone in a young person's room (Bullerjahn, 2005); (4) Most research designs are too complicated and extensive.…”
Section: Soundtrack and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Vor über 25 Jahren wurde infolgedessen das Musical-Fit-Konzept entwickelt, um zu konkretisieren, wie Musik in der Werbung effektiv eingesetzt werden kann (Macinnis & Park, 1991). Definiert wird Musical Fit von Macinnis und Park wie folgt: "consumer's subjective perception of the music's relevance or appropriateness to the central ad message" ii (Macinnis & Park, 1991, S. 162 (Allan, 2007;Oakes, 2007 (Bullerjahn, 2001;Cohen, 2010;Evans & Schubert, 2008) und durch das Auslösen spezifischer Assoziationen Bedeutung vermitteln kann (Herget, 2019) (Herget et al, 2018(Herget et al, , 2020.…”
Section: Prosoziale Musik In Sozialer Werbung Einsatz Und Wirkung Vonunclassified